Construction drawings and details for interiors : - Kilmer, W. Otie (J. Wiley, 2003)
Get a realistic guide to producing construction documents that clearly communicate the interior space of new construction, remodeling, or installation projects with Construction Drawings and Details for Interiors. This highly visual book: includes such details as furniture, finishes, lighting, and others; features authors drawings as well as those from practicing professionals; covers drafting fundamentals and conventions; drawing types, plans, and schedules; and computer-aided design; addresses graphic language as a communication tool; details the process of creating construction documents, the use of computers, and various reproduction systems and standards; includes examples of both residential and commercial interiors.